Changes in soft tissue profile and electromyographic activity after activator treatment - Erdem Abdulvahit; Kilic Nihat; Eröz Barçin (Sciendo, 2023)
To date, few studies have correlated the changes in muscle activity and specific soft tissue variables in adolescents with malocclusions.